Rethinking voluntary approaches in environmental policy - Sullivan, Rory, 1968-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2005)
The book systematically analyses three initiatives (environmental management systems, the Australian Greenhouse Challenge and the Australian mining industry's Code for Environmental Management) and their contribution to public environmental policy. By moving the debate away from narrow considerations of economic efficiency towards a broader framework that accounts for the multiple goals to which environmental policy needs to be directed, this book significantly enhances our understanding of the role that voluntary approaches can play in achieving environmental policy goals.
pt. 1. Introduction -- pt. 2. Literature review -- pt. 3. Voluntary approaches in Australia -- pt. 4. Synthesis and analysis.
Based on author's thesis (Ph. D.--University of London) originally presented under the title: An assessment of the role of voluntary apporaches in public environmental policy.
Includes bibliographical references.
Keywords: Environmental policy -- Australia; Industries -- Environmental aspects -- Australia -- Case studies; Electronic books